2019
DOI: 10.1016/j.molcel.2019.01.035
|View full text |Cite
|
Sign up to set email alerts
|

FIP200 Claw Domain Binding to p62 Promotes Autophagosome Formation at Ubiquitin Condensates

Abstract: Highlights d p62 directly interacts with the FIP200 C-terminal domain d Structural studies reveal a claw shape of the conserved FIP200 C-terminal domain d p62-ubiquitin condensates recruit FIP200 via the Claw to promote their degradation d LC3B outcompetes FIP200 from p62, suggesting an inbuild directionality in the system

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
309
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 245 publications
(346 citation statements)
references
References 59 publications
(91 reference statements)
16
309
0
Order By: Relevance
“…We have now confirmed that the CC projects away from the center of the NTD. Thus, the symmetry of the NTD matches the symmetry of the FIP200 CC, which is parallel and a dimer (Turco et al, 2019). FIP200 CC has a modal end-toend distance of ~75 nm and is partially flexible, making it ideally suited to its function of connecting cargo to other components of the ULK1 complex and to membranes over substantial distances, much as seen with other coiled-coil based tethers such as the endosomal tether EEA1 (Murray et al, 2016)and the Golgi tether GCC185 (Cheung & Pfeffer, 2015).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…We have now confirmed that the CC projects away from the center of the NTD. Thus, the symmetry of the NTD matches the symmetry of the FIP200 CC, which is parallel and a dimer (Turco et al, 2019). FIP200 CC has a modal end-toend distance of ~75 nm and is partially flexible, making it ideally suited to its function of connecting cargo to other components of the ULK1 complex and to membranes over substantial distances, much as seen with other coiled-coil based tethers such as the endosomal tether EEA1 (Murray et al, 2016)and the Golgi tether GCC185 (Cheung & Pfeffer, 2015).…”
Section: Discussionmentioning
confidence: 71%
“…Recognition of p62 (Turco et al, 2019) and NDP52 (Vargas et al, 2019) by FIP200 was shown to the key triggering event responsible for recruiting the ULK1 complex to cargo. The binding sites of p62 and NDP52 were mapped to the Claw (Turco et al, 2019) and CC C-terminus (Ravenhill et al, 2019) respectively, and the structure of the Claw and a small part of the CC were determined (Turco et al, 2019). All of the many downstream events remained unclear, however, as did the structure of the great majority of FIP200.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parkin-mediated poly-ubiquitination of outer mitochondrial membrane proteins triggers the recruitment of autophagy receptors such as optineurin (OPTN), calcium binding and coiled-coil domain 2 (CALCOCO2, better known as NDP52) and Tax1 binding protein 1 (TAX1BP1), concomitantly with the activation of the TANK binding kinase 1 (TBK1) that phosphorylates OPTN (at serine 177, 473, and 513) further enhancing its ubiquitin chain binding ability (Wild et al, 2011;Wong and Holzbaur, 2014;Heo et al, 2015;Lazarou et al, 2015). Once recruited to the mitochondria, autophagy receptors can employ initiator proteins from the autophagic machinery such as unc-51 like autophagy activating kinase 1 (ULK1), zinc finger FYVE-type containing 1 (ZFYVE1, better known as DFCP1) and WD repeat domain, phosphoinositide interacting 1 (WIPI1, also known as ATG18) to assemble the autophagosome (Wong and Holzbaur, 2014;Lazarou et al, 2015;Ravenhill et al, 2019;Turco et al, 2019;Vargas et al, 2019) and ATG8s, which could further recruit autophagy receptors to amplify mitophagy signals (Padman et al, 2019). The key function of the ULK1-containing complex for selective autophagy has been recently discussed elsewhere (Turco et al, 2020).…”
Section: Pink1 and Parkin-regulated Mitophagymentioning
confidence: 99%
“…Client proteins are polyubiquitinated by the E3 ligase STUB1/ CHIP (STIP1 homology and U-box containing protein 1) and subsequently sequestered into cytoplasmic puncta that are labeled with SQSTM1/p62 (also called p62 bodies). SQSTM1/p62 functions as a multi-adaptor protein by binding simultaneously to ubiquitin and the autophagosome-associated protein MAP1LC3/ LC3 (microtubule associated protein 1 light chain 3), allowing misfolded proteins to be inserted into autophagosomes, followed by lysosomal degradation (Ciuffa et al 2015;Wurzer et al 2015;Cha-Molstad et al 2017;Zaffagnini et al 2018;Turco et al 2019). Overexpression of wild-type HSPB8 in neuronal cells led to an increased colocalization of autophagosomes with lysosomes while overexpression of mutant HSPB8 (K141N) reduced colocalization between autophagosomes and lysosomes (Kwok et al 2011).…”
Section: Hspb8mentioning
confidence: 99%